2004
DOI: 10.1002/uog.964
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal abnormalities in fetuses with open neural tube defects: prenatal identification with ultrasound

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
29
7
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 31 publications
4
29
7
2
Order By: Relevance
“…The most frequent chromosome abnormality was trisomy 18 (15/27, 56%). Our results showed a slightly higher frequency of chromosome abnormalities than the 5-10% rate in other studies [31,32,33]. Moreover, the distribution of chromosomally abnormal cases varied depending on the type of fetal defect.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…The most frequent chromosome abnormality was trisomy 18 (15/27, 56%). Our results showed a slightly higher frequency of chromosome abnormalities than the 5-10% rate in other studies [31,32,33]. Moreover, the distribution of chromosomally abnormal cases varied depending on the type of fetal defect.…”
Section: Discussioncontrasting
confidence: 54%
“…Moreover, the distribution of chromosomally abnormal cases varied depending on the type of fetal defect. In our study, 18% (18/100) of cases with spina bifida had chromosomal abnormality, which was clearly higher than the 8-10% reported in the above-cited papers [31,32,33] but in accordance with the 16-20% rates reported in two others [29,30]. Chromosomal abnormality was found in 10% of anencephaly: this contrasted with the study of Sepulveda et al [33] who reported only one chromosomal abnormality among 57 cases of anencephaly.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Abnormal migration, proliferation and differentiation of these cells results in congenital malformation in this region. 19 This type of fused truncus was noted in one case of craniorachischisis. Although, there was a slight groove externally, there was no ridge internally (7.69%).…”
Section: However Nakatsu Et Al (2000) Observed 3 Sites Ofmentioning
confidence: 95%
“…Típicamente, se describen como anomalías de origen multifactorial (poligénico-ambiental), aunque en algunos casos existe asociación con ciertos síndromes genéticos (Meckel-Gruber, Jarcho-Levine, Wardenburg) o con anomalías cromosómicas (trisomía 18). En nuestro medio se ha comunicado una prevalencia de anomalía cromosómica en DTN de 2% para anencefalia, 9% para espina bífida y de 14% para cefalocele 2 .…”
unclassified